Wpływ procesu starzenia się ludności na ryzyko w ubezpieczeniach na życie - Papież, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents an analysis of the influence of ageing process of the population on the assessment of the products of insurance companies regarding living benefits, and, at the same time, on the risks connected with such assessment. In the assessment and management of living benefits two fundamental risk sources play a fundamental role: the investment risk and the demographic risk. The demographic risk is divided in two components: the insurance risk and the longevity risk. The longevity risk is particularly important; it derives from improvements in mortality trend, which determine systematic deviations of the number of deaths from its expected values. This risk should be assuaged by replacing traditional mortality tables used in the assessment of insurance products with projected mortality tables, which include a forecast of the future trends in mortality. The paper also presents Lee & Carter model for describing the secular change in mortality as a function of a single time index, which can be used to assess the values in projected mortality tables. In fact, a complete investigation of the effects due to the longevity risk can be reached only by framing it in a stochastic point of view; in other words, the more concrete approach to this problem consists in studying the impact of the random improving dynamic of mortality rates and their effects on portfolio's management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 298-307